English Skills Based Microteaching: An Effective Model in Enhancing English Student Teachers’ Teaching Skills - Darmayenti, Darmayenti; Besral, Besral; Kustati, Martin (AT-TA'LIM, 2019)
Building basic teaching and English skills for student teachers need appropriate and effective teaching model. The current study aimed at designing a model of Micro-teaching Based-English Skill for undergraduates English program at State Islamic University. Research and Development type was used to develop the model. The subjects of this study were seven groups of students (each consist of 12 students) and seven lecturers.  Two groups were cluster randomly selected participate in this study. Pre-test and post-test design of experimental research model has been used without the control group and followed by treatment for 8 weeks prior to their teaching practice in the nearby schools. Data were taken from observations, questionnaires, and test.  The results showed that Micro-teaching Based-English Skill model was appropriate for the lecturers and students. The students’ basic teaching and their English skills were better improved. Therefore, this model is suggested to be implemented provided that both English skills and pedagogical one were the major expectation to be reached.